PERAN GURU DALAM STRATEGI PEMBELAJARAN MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Yusnita Hikmawati; Muhammad Fajrul Falah; Badrani Dhyal Haqi; Nur Laila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACTThis study explores the contribution of learning media, classroom atmosphere, feedback, and learning outcome evaluation in enhancing students’ learning motivation in Islamic Religious Education (PAI) at the elementary school level. The research employs a qualitative descriptive approach through literature review and classroom observations. The findings indicate that the effective use of learning media, the creation of a supportive classroom environment, the provision of constructive feedback, and the implementation of systematic evaluation practices play an important role in fostering students’ motivation to learn. Teachers who are able to integrate these four elements effectively can provide learning experiences that are more engaging, meaningful, and conducive to student development. The study concludes that the harmonious interaction between learning media, classroom climate, feedback, and evaluation serves as a strategic foundation for achieving PAI learning objectives across cognitive, affective, and psychomotor domains.Keywords: learning media, classroom atmosphere, feedback, evaluation, Islamic Religious Education